Understanding a mother's love: the influence of maternal warmth on the relationship between harsh parenting practices and child behavioural outcomes - Leong, Amanda Wai Mun (Nanyang Technological University, 2024)
Darling and Steinberg argue that parenting styles form the global context of the parent-child relationship and therefore, alter the meaning of parenting practices and its relation to child outcomes. In Singapore, harsh parenting practices (physical punishment and guilt induction) remain normative despite its associations with negative outcomes. Therefore, it is valuable to examine if a warm parenting style alters the meaning of these harsh practices and its association to poorer child outcomes. Comprising of mother-child dyads, Study 1 examines the relationship between harsh parenting practices (physical punishment and guilt induction) and child behavioural outcomes (externalising and internalising behaviours) with warmth as a moderator. Gender was included as a covariate for externalising behaviours. Study 2 aims to understand how warmth is demonstrated and perceived in Singapore through analysing a subset of interviews from mothers and children. From Study 1, it was found that higher levels of physical punishment and guilt induction were related higher levels of externalising and internalising behaviours. While greater warmth were associated to lower levels of externalising behaviours, it was not associated to lower levels of internalising behaviours. No moderating effect for warmth was found. Study 2 reported some discrepancies in how warmth was demonstrated by mothers and perceived by children. Future studies can therefore consider the child’s perception of maternal warmth as a moderator and look into adapting existing warmth scales to be more inclusive of a variety of expressions of acceptance and warmth.